INOVASI PEMBUATAN ABON IKAN CAKALANG DENGAN PENAMBAHAN JANTUNG PISANG - Andi Muhammad Ismail; Dhanang Eka Putra (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2017)
Innovation is needed in all areas including the processed agribusiness fisheries. The purpose of this study was to innovate a skipjack tuna product with the addition of banana heart abon. The sample of this study used 30 panelists with vulnerable age of 25-40 years with a sample of concentration of banana heart addition by 0%, 30%, 50%, 70%. Instrument used in this research is koesioner. Univarit and bivarite data analysis (One Way Anova and Friedman with alpha of 0,05). The results of this study found that abon skipjack tuna with the addition of a banana heart of 30% gives the preferred level to the panelist larger by an average of 4.04% of the abon without the heart and 50% and 70% banana heart abon. Result of normality test with Friedman test in can that there is influence of concentration of banana heart addition to aspect of color, taste, texture and aroma abon skipjack tuna.